2017
DOI: 10.37757/mr2017.v19.n2-3.4
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Surgery Case Fatality and Associated Factors in a Cuban Pediatric Hospital, 2005–2015

Abstract: INTRODUCTION Newborns in need of surgery are a challenge to manage and require highly specialized centers with multidisciplinary surgical teams. Since the 1980s, neonatal surgical survival has increased by up to 70% in some countries, mainly due to advances in neonatal intensive care, anesthesia and surgical technique. OBJECTIVE Describe surgical case fatality and survival in a neonatal reference hospital in Cuba, estimate risk of death, and identify potential risk predictors among neonatal characteristics.MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Sepsis (31.4%) was the most common postoperative complication in this study, which matches ndings from studies in Alexandria(18) and Tunisia (19) that found wound sepsis (53.8 %) and epsis secondary to hospital-acquired infection (36.3 %) to b the most common postoperative complications, respectively. Wound sepsis is preventable but, despite advances in surgical technique, continues to be one of the main challenges in neonatal surgery (20). This can be due to similar facilities in developing countries and paucity of skilled man power, material resources, and scarcity of interdisciplinary collaborations.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis (31.4%) was the most common postoperative complication in this study, which matches ndings from studies in Alexandria(18) and Tunisia (19) that found wound sepsis (53.8 %) and epsis secondary to hospital-acquired infection (36.3 %) to b the most common postoperative complications, respectively. Wound sepsis is preventable but, despite advances in surgical technique, continues to be one of the main challenges in neonatal surgery (20). This can be due to similar facilities in developing countries and paucity of skilled man power, material resources, and scarcity of interdisciplinary collaborations.…”
Section: Discussionmentioning
confidence: 99%